Clinical Efficacy of Short-Term Peripheral Nerve Stimulation in Management of Facial Pain Associated With Herpes Zoster Ophthalmicus - Han, Rui; Guo, Gangwen; Ni, Yuncheng; Wang, Ziyang; Yang, Liuqing; Zhang, Jianping; Li, Xuelian; Hu, Rong; Huang, Dong; Zhou, Haocheng (Frontiers in Neuroscience, 2020)
Objective Peripheral nerve stimulation may be an alternative option to treat severe facial pain. We assessed the application of peripheral nerve stimulation for pain management in patients with herpes zoster ophthalmicus. Method A retrospective analysis was conducted in patients suffering severe facial pain caused by ophthalmic herpetic lesions. We identified the change in pain severity before and after peripheral nerve stimulation for up to 12 months. Results Eighteen patients were enrolled. Their mean age was 70.8 ± 9.5 years. Fifteen patients presented with subacute pain for 1–3 months, and three patients suffered postherpetic neuralgia. Dramatic relief from pain was achieved in 83% of patients (15 out of 18) upon initial removal of the stimulator, with pain reduction of > 50%. The long-term analgesic effect was reported at the 6- and 12-month follow-ups, with reductions in the visual analog scale of 4.8 ± 1.2 (n = 18) and 5.4 ± 1.4 (n = 11), respectively. The prevalence of postherpetic neuralgia was 7% (1 out of 15) in the subacute pain group. No obvious adverse effect was observed. Conclusion Peripheral nerve stimulation may be an efficacious and safe approach for pain control in patients with herpes zoster ophthalmicus.